Implementasi Lembar Kerja Siswa Kurikulum 2013 Bidang IPA Di SMP Muhammadiyah 4 Sambi Tahun Ajaran 2014/2015 - Munawaroh, Siti; , Dr. Sofyan Anif, M.Si (2015)
The worksheet student in 2013 curriculum learning is an activating learning method for student. However, in the fact, the teachersdo not use the worksheet student in learning activities and just apply a talkative strategy (teacher center). It will influencethe students' skill. This study aims to understand the implementation level and describe the implementation of 2013 curriculum worksheet student in science lesson. Besides that, it also aims to identify the influencing factors of science worksheet in 2013 curriculum at Muhammadiyah 4 Sambi Junior High School in Boyolali. This research uses descriptive qualitative method and case study strategy research. The subject of the study is a headmaster and the teachers of Muhammadiyah 4 Sambi Junior High School in Boyolali. The technique of collecting data is observation, documentary and interview. The technique of analyzing data is transcription technique, data organization and drawing the conclusion. Based on this study, it can be obtained that, the implementation of curriculum 2013 worksheet student in science book at Muhammadiyah 4 Sambi Junior High School is 9,25%. The implementation of worksheet student is relatively very low. The worksheet student application is very low because of some factors, such as: the school infrastructure is inadequate, the lack of teachers' ability to develop worksheet and human resources. There is no control about worksheet student from Ministry of National Education during the implementation of learning using 2013 curriculum. Based on the result of this study, the 2013 curriculum worksheet student in science lesson is not applied. Therefore, the students' skill won't develop. They just focused on material comprehension without practicum activities because the teachers are more use talkative strategy (teacher center).